Pengaruh Money Ethics, Pemahaman Tri Pantangan DAN Tax Evasion: Religiusitas Sebagai Pemoderasi - Asri Solikah (Yayasan Literasi Ilmiah Indonesia, 2022)
Purpose: This research aims to prove whether money ethics and understanding of the tri pantangan have an effect on tax evasion with the moderating variable of religion. Method: This study uses a quantitative description method and primary data using a questionnaire. This study was 136 samples, the samples is students of the University of Sarjanawiyata Tamansiswa as taxpayers. Sampling in this study used a snowball sampling technique. Finding: Money ethics has no effect on tax evasion, understanding of tri pantangan has no effect on tax evasion, religiosity is able to weaken the positive effect of money ethics on tax evasion, and religiosity can strengthen the negative effect of understanding tri pantangan on tax evasion. Novelty: This study adds a variable understanding of tri pantangan to prove, how students of the University of Sarjanawiyata Tamansiswa can practice the teaching of Tamansiswa in tax evasion actions.